Comparison of indirect fluorescent antibody test and modified agglutination test for detecting Toxoplasma gondii immunoglobulin G antibodies in dog and cat - Macrì, Gladia; Sala, Marcello; Linder, Alicia M; Pettirossi, Nadia; Scarpulla, Manuela (Parasitology research (1987), 2009)
The present study describes the comparison between a modified agglutination test (MAT) and the indirect fluorescent antibody test (IFAT) for the detection of Toxoplasma specific IgG antibodies in dog and cat sera. MAT showed an “almost perfect” agreement with IFAT in detecting positive and negative results in cat sera, where as only a “substantial” agreement was observed in dog sera due to false negative results. Differences relative to sample dilution were recorded and serological titres obtained by MAT and IFAT are not directly comparable in cat and dog sera.